Establishment Methods and Weed Management Effects on Productivity and Soil Fertility in Wetland Rice (Oryza sativa L.) - and D.C. Kalita, M. Mokidul Islam (Journal of the Indian Society of Soil Science, 2015)
Field experiments in 2010 and 2011 was conducted to evaluate the effect of integrated weed management practices on productivity, nutrient uptake, nutrient harvest index and residual soil fertility status in wetland rice (Oryza sativa L.) under different establishment methods. Wetland rice under system of rice intensification (SRI) method gave significantly higher grain productivity. However, hand weeding twice at 20 and 40 days after transplanting (DAT) was similar with butachlor 50 EC at 1.5 kg a.i. ha-1 at 3 DAT + cono-weeding at 20 DAT. Total uptake of N, P and K by wetland rice was recorded higher with SRI followed by integrated crop management and conventional rice culture. Hand weeding twice at 20 and 40 DAT recorded significantly higher N, P and K uptake in grain and straw followed by butachlor 50 EC at 1.5 kg a.i. ha-1 at 3 DAT + cono-weeding at 20 DAT. The highest nitrogen harvest index (NHI), phosphorus harvest index (PHI) and potassium harvest index (KHI) (79.8, 58.8 and 36.6%), respectively were recorded with cono-weeding twice at 20 and 40 DAT. The residual soil pH, OC, MBC and available N, P and K was significantly higher in SRI method with hand weeding twice at 20 and 40 DAT. Hence, integrated weed management with butachlor 50 EC at 1.5 kg a.i. ha-1 + cono-weeding at 20 DAT performed well under SRI method. However, hand weeding twice at 20 and 40 DAT performed better under ICM method in terms of productivity and better soil health in wetland rice ecosystem.